Transfer of Maternal Immunity to Newborns of Diabetic Mothers - Eduardo Luzía França; Iracema de Mattos Paranhos Calderon; Elisa Lima Vieira; Glilciane Morceli; Adenilda Cristina Honorio-França (Clinical and Developmental Immunology)
This study was carried out with hyperglycemic pregnant women to investigate the transfer of antibody classes to newborns across the placenta or by colostrum and the functional activity of phagocytes in maternal blood, cord blood, and colostrum from diabetes mothers. Samples from maternal blood, cord blood, and colostrum were collected from 20 normoglycemic and 20 hyperglycemic pregnant women. We determined antibodies levels, superoxide release, phagocytosis and bactericidal activity of phagocytes. We demonstrated that IgG levels in cord blood were higher in the hyperglycemic group. IgA and IgM levels were higher in maternal than in cord blood samples. Plasma antibody levels were lower in hyper- than in normoglycemic women. The colostrum of diabetic mothers had lower IgA and IgG levels. Colostrum and maternal blood phagocytes when exposed to EPEC increased the superoxide release. Cord blood phagocytes of hyperglycemic group, independently of bacteria, had higher superoxide release. Colostrum and blood phagocytes from diabetic group exhibited some phagocytic and microbicidal activity in response to EPEC. Mononuclear phagocytes from cord blood had the lowest phagocytosis, and bactericidal activity for EPEC, regardless of glycemic status. These data showed that hyperglycemia altered IgG transfer across the placenta and decreases immunoglobulin levels in maternal blood and colostrum.